Accuracy and variability of semiautomatic centerline analysis versus manual aortic measurement techniques for TEVAR - Müller-Eschner, Matthias; Rengier, Fabian; Partovi, Sasan; Weber, Tim; Kopp-Schneider, Annette; Geisbüsch, Philipp; Kauczor, Hans-Ulrich; Tengg-Kobligk, Hendrik von (European journal of vascular and endovascular surgery, 2013)
Objectives - This study aims to test whether inter-observer variability and time of diameter measurements for thoracic endovascular aortic repair (TEVAR) are improved by semiautomatic centerline analysis compared to manual assessment. - Methods - Preoperative computed tomography (CT) angiographies of 30 patients with thoracic aortic disease (mean age 66.8 ± 11.6 years, 23 males) were retrospectively analysed by two blinded experts in vascular radiology. Maximum aortic diameters at three positions relevant to TEVAR were assessed (P1, distal to left common carotid artery; P2, distal to left subclavian artery; and P3, proximal to coeliac trunk) using three measurement techniques: manual axial slices (axial), manual double-oblique multiplanar reformations (MPRs) and semiautomatic centerline analysis. - Results - Diameter measurements by both centerline analysis and the axial technique did not significantly differ from MPR (p = 0.17 and p = 0.37). Total deviation index for 0.9 was for P1 2.7 mm (axial), 3.7 mm (MPR), 1.8 mm (centerline); for P2 2.0 mm (axial), 3.6 mm (MPR), 1.8 mm (centerline); and for P3 3.0 mm (axial), 3.5 mm (MPR), 2.5 mm (centerline). Measurement time using centerline analysis was significantly shorter than for assessment by MPR. - Conclusions - Centerline analysis provides the least variable and fast diameter measurements in TEVAR patients with the same accuracy as the current reference standard MPR.
Gesehen am 22.06.2021